Komparasi Hukum Pernikahan Anak Perempuan Yatim di Bawah Umur Oleh Selain Wali Mujbir Menurut pandangan Imam Abu Hanifah dan Pandangan Imam Malik - Putri Syam , Aisyah; Adly, M.Amar (LPPM Universitas Ekasakti Padang, 2023)
Guardians are one of the most important components in marriage. The presence of a guardian is a determining factor in the legitimacy of the marriage. In the view of some people, perhaps someone's trust is considered too great, given the right of a guardian who can force his child to marry without having to ask for the child's consent. Under the pretext of freedom to choose their own partners, so many people think that the rights of guardians in modern times need to be reviewed and some even think it is not worth implementing. This short article tries to disentangle views by exposing the opinions of scientists regarding the rights and position of guardians in marriage. This research method uses a normative juridical method, namely an approach that looks at a law or a set of regulations that are normative in nature (law in book). the scholars. The method used in this research is the analytical method. This type of research is library research, where the sources are obtained by searching scientific journal articles and books related to the topic of discussion.